Alternatif Media Pendidikan Politik Dalam Rangka Membangun Partisipasi Politik Pemuda Tani - Dea Christina; Peinina Ireine Nindatu; Djuara P. Lubis (Jurnal Komunikasi Pembangunan, 2016)
This article discuss a strategy to increase farmer youth political participation through their involvement in some organization, such as community-based organization; farmer mass organization; and activity-based organization. However, it is believe another strategy that have not been used optimally for the purpose of gaining farmer youth political awareness and participation. It is the new media, which acknowledged as online/ social media. This media is usually used by farmer limited for their farming activities, either searching cultivation or market information. Whereas, this media has a lot of advantage that the conventional methods have not, such as its ability to reach people farther, short the time, and deal with socio-cultural lack in the community. Based on literature study, this media actually has a significant role in developing awareness and political participation of the youth, especially urban or metropolis youth. However, is it also influence the political behaviour of urban or farmer youth?Keywords: Farmer Youth, Political Participation, Political Socialization Media